Cardiovascular End Points and Mortality Are Not Closer Associated With Central Than Peripheral Pulsatile Blood Pressure Components - Huang QF; Aparicio LS; Thijs L; Wei FF; Melgarejo JD; Cheng YB; Sheng CS; Yang WY; Gilis-Malinowska N; Boggia J; Niiranen TJ; Wojciechowska W; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Pulsatile blood pressure (BP) confers cardiovascular risk. Whether associations of cardiovascular end points are tighter for central systolic BP (cSBP) than peripheral systolic BP (pSBP) or central pulse pressure (cPP) than peripheral pulse pressure (pPP) is uncertain. Among 5608 participants (54.1% women; mean age, 54.2 years) enrolled in nine studies, median follow-up was 4.1 years. cSBP and cPP, estimated tonometrically from the radial waveform, averaged 123.7 and 42.5 mm Hg, and pSBP and pPP 134.1 and 53.9 mm Hg. The primary composite cardiovascular end point occurred in 255 participants (4.5%). Across fourths of the cPP distribution, rates increased exponentially (4.1, 5.0, 7.3, and 22.0 per 1000 person-years) with comparable estimates for cSBP, pSBP, and pPP. The multivariable-adjusted hazard ratios, expressing the risk per 1-SD increment in BP, were 1.50 (95% CI, 1.33-1.70) for cSBP, 1.36 (95% CI, 1.19-1.54) for cPP, 1.49 (95% CI, 1.33-1.67) for pSBP, and 1.34 (95% CI, 1.19-1.51) for pPP (P<0.001). Further adjustment of cSBP and cPP, respectively, for pSBP and pPP, and vice versa, removed the significance of all hazard ratios. Adding cSBP, cPP, pSBP, pPP to a base model including covariables increased the model fit (P<0.001) with generalizedR(2)increments ranging from 0.37% to 0.74% but adding a second BP to a model including already one did not. Analyses of the secondary end points, including total mortality (204 deaths), coronary end points (109) and strokes (89), and various sensitivity analyses produced consistent results. In conclusion, associations of the primary and secondary end points with SBP and pulse pressure were not stronger if BP was measured centrally compared with peripherally.